(untitled) (Zoological Records and Reviews, 2025)
Long-term biodiversity monitoring programs (LTBMPs) are the foundational infrastructure for detecting population trends, evaluating conservation policy effectiveness, and understanding ecosystem responses to global environmental change. Yet the global portfolio of LTBMPs is severely uneven in geographic coverage, taxonomic scope, methodological consistency, and data accessibility, limiting the capacity to detect biodiversity change at scales relevant to international policy frameworks. This review synthesises evidence from 178 primary studies and programme evaluations (2000-2025) examining the design, performance, and policy relevance of LTBMPs across terrestrial, freshwater, and marine ecosystems, with a focus on European monitoring infrastructure. We evaluate 24 major European and global LTBMPs across six performance dimensions: temporal coverage, spatial replication, taxonomic breadth, methodological consistency, open data provision, and policy linkage. The UK Countryside Survey and Swiss Biodiversity Monitoring programme achieve the highest overall performance scores (composite 2.72 and 2.68/3.0 respectively), distinguished by multi-taxon design, consistent long-term protocols, and direct policy linkage. A critical analysis identifies five structural deficiencies common to European monitoring: inadequate freshwater invertebrate coverage outside WFD obligations, near-absence of soil biodiversity monitoring, insufficient taxonomic expertise to sustain morphological identification programmes, geographic gaps in Southern and Eastern Europe, and funding cycle mismatches that interrupt time series at critical junctures. Emerging solutions – citizen science integration, eDNA metabarcoding, automated acoustic monitoring, and open data platforms (GBIF, LTER-Europe) – are evaluated for their capacity to address these deficiencies. A design framework for next-generation European biodiversity monitoring is presented.